A Highly Sensitive Flame Emission Spectrophotometric Method for the Determination of some Phenothiazine Antipsychotics via Potassium Dichromate as Oxidant Reagent (Journal of the College of Basic Education, 2023)
A flame emission method here is described for the determination of phenothiazines. The method based on the oxidation of phenothiazines in an acid medium to colorless sulfoxides via orange or purple-colored intermediates. In the begin employs flame emission spectrophotometric potassium intensity detection. The proposed method was successfully applied to the determination of phenothiazine in pharmaceutical preparations. The reliability of the assay was established by parallel determination by the official methods of British Pharmacopoeia.The optimum reaction conditions and other analytical parameters are evaluated.